An Epochal Analysis on Colonial Trauma in Independent Documentaries: Jeju Prayer as Study Case - Makbul Mubarak (ULTIMART Jurnal Komunikasi Visual, 2017)
This paper departs from Raymond Williams’ notion of ‘epochal analysis,’ an analysis that functions to see a cultural process as a cultural system in the dialectic of the dominant, the residual, and the emergent. It is true that what Williams meant by ‘the dominant’ in his proposition is either the feudal culture and the bourgeois culture and their transition, but he also says that the epochal analysis functions to sense a movement in its connection to the future and the past. Williams wrote (1978, p. 121): “…Its methodology is preserved for the very different function of historical analysis, in which a sense of movement within what is ordinarily abstracted as a system is crucially necessary, especially if it is to connect with the future as well as with the past. Keywords : documentary, trauma, dominant fiction, psychoanalysis